Analysis of the influence of Multichannel Marketing Strategy in the 5.0 era: Integrating Online and Offline for Optimal Results - Santoso, Fuji; Sudarmiatin, Sudarmiatin (Journal of Business Management and Economic Development, 2024)
This research aims to analyze the influence of multichannel marketing strategies in the 5.0 era that integrate online and offline to achieve optimal results. Multichannel marketing has become an important approach in the face of advances in digital technology and growing connectivity. The integration of online and offline in a multichannel marketing strategy allows companies to reach a wider range of consumers, provide consistent and holistic experiences, and leverage data and analytics to understand consumer preferences and behaviors. However, implementing a multichannel marketing strategy is not easy and requires adequate technological infrastructure, skilled human resources, and good coordination. This research method will use a quantitative approach by collecting data from respondents consisting of consumers who have interacted with multichannel marketing strategies. The results of this study provide insights into the importance of online and offline integration in multichannel marketing strategies in the 5.0 era, as well as practical implications for companies in optimizing their marketing efforts. This research can be an important reference for companies that want to improve their marketing performance by leveraging the power of both channels.